Evolução da Estratégia Saúde da Família em Mato Grosso e sua influência nos indicadores da Atenção Básica em Saúde no período de 2008 a 2015 - Fonseca, Juliane Ferreira Andrade da [UNIFESP] (2018)
Introduction: The Family Health Strategy implemented by the Ministry of Health with principles and concepts of primary health care with the purpose of changing the way services are organized, care practices focused on family and community. The many professionals team in its work process develops activities that will generate indicators that can subsidize the planning of interventions according to the local health needs. Objective: To analyze the influence of the Family Health Strategy on indicators of basic health care according to its structure, process and outcome components in the municipalities of Mato Grosso, from 2008 to 2015. Method: This is an evaluative research, quantitative, retrospective analysis using secondary data from the federal government's official information systems. A matrix was built consisting of structure components (potential population coverage), process (medical consultation, home visit of doctor and nurse, referral to specialist and request for clinical pathology exams) and outcome (hospitalization rate due to causes sensitive to primary care, proportion of live births of mothers with seven or more prenatal consultations and infant mortality coefficient). The descriptive analysis and Spearman Correlation coefficient (rho) were made. Results: The study indicated that the population coverage always remained high, above 83%, the process indicators suggest an improvement in the specialist, a reduction of 49.71 % in the average number of requests for clinical pathology exams, but there was also a reduction of 7.13% in the average home visit in the period studied. There is correlation between the structure and process component and between structure and result. The correlation between population coverage and hospitalization rate for causes sensitive to primary care showed a divergent positive association with other studies. Conclusions: The research showed that with the evolution of the family health strategy there were changes in some indicators of primary care in Mato Grosso demonstrating the accessibility to the service, effectiveness and positive effects on the health of the population. Regarding the correlation of the components of structure and process and of structure and result, it was pointed out to be a management tool for evaluation of the program.